Choice of a suicide method: Trends and characteristics. (February 2018) - Kõlves, Kairi; McDonough, Matthew; Crompton, David; de Leo, Diego
Abstract: The aim of this study was to examine (1) suicide trends by most prevalent methods in Queensland, Australia, during 2000–2015, and (2) characteristics of people by choice of suicide method in 2000–2013. Data were obtained from the Queensland Suicide Register, which includes police and toxicology reports, post-mortem autopsy and Coroner's findings. Poisson and Joinpoint regression were used to study the first aim, and uni-variate and multi-variate logistic regression analyses were applied to investigate the second aim. Suicide method trends showed a significant increase in hanging for both sexes and poisoning with drugs for females, while there was a decline for poisoning by other means for both sexes, and 'other methods' decreased for males. Changes in the trends have altered the order of suicide methods, especially in males. Analyses of 8140 suicides were composed by the choice of method, distinguishable profiles by their demographic, clinical and social characteristics, such as having mental or physical illness or different recent life stressors were identified. This suggests that socio-cultural acceptability, and availability are the key drivers in the choice of suicide methods. Continuing increases in hanging is a big challenge in suicide prevention due to its lethality, easy realisation and its increasing acceptability. Highlights: Different suicide methods have distinguishable profiles by individual characteristics. The biggest future challenge of suicide prevention will be the increase in hanging. Changes in the prevalence have altered the order of different suicide methods used between 2000 and 2015.